The Use of Hanging Bottle Media in Improving Pencak Silat Front Kick Skills among Seventh-Grade Students - Puji Lestari; Norma Anggara; Syamsul Arifin; Recky Ahmad Haffyandi (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to determine the effect of using hanging bottles as a training aid on Pencak Silat front kick skills among seventh-grade students. This research was prompted by students’ low proficiency in performing front kick techniques, as evidenced by incorrect kick direction, poor balance, and suboptimal motor coordination. Methods – This study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 26 seventh-grade students. The instrument used was a practical test assessing front kick skills based on movement technique indicators. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank Test, and N-Gain analysis. Findings – The results revealed a significant improvement between pretest and posttest scores, with an asymptotic significance value of p < 0.001. The mean pretest score increased from 43.65 to 86.15 on the posttest. Furthermore, the average N-Gain value of 0.76 (76.47%) fell into the "high" and "effective" categories. These findings indicate that hanging bottle media can help students achieve specific learning goals, improve concentration, and refine movement techniques.Research Implications – Therefore, hanging bottle media serves as an innovative and effective instructional alternative for improving front kick skills in Pencak Silat within the Physical Education (PJOK) curriculum. However, this study is limited to a specific student sample at a single grade level and focuses solely on one technique, the front kick. Consequently, its effectiveness across other age groups or kick types cannot yet be generalized.